Periprocedural myocardial injury during elective percutaneous coronary intervention: is it important and how can it be prevented?. Issue 10 (6th May 2010) - Cuculi, F; Lim, C C S; Banning, A P
Abstract : Periprocedural myocardial injury (PMI) is common after percutaneous coronary intervention (PCI). Periprocedural infarction (myocardial infarction type 4a) occurs after at least 10% of PCI procedures and has an impact on long-term prognosis. Measurement of biomarkers to allow assessment of PMI is an important tool for clinical and research purposes and should be routine after every PCI (troponin I or T and CK-MB). The importance of oral and intravenous antiplatelet agents and other drugs which have been proven to reduce PMI is discussed.